Freedom to Learn and Freedom to Teach in Science Learning through ChatGPT: Systematic Literature Review - Paulus L Wairisal; Elijonnahdi Elijonnahdi; Nugroho Susanto; Ruth Rize Paas Megahati S (Jurnal Penelitian Pendidikan IPA, 2023)
Education is very important in preparing people to be able to maintain and improve the quality of life as individuals with dignity. The severity of the challenges faced in all fields can be seen from various kinds of reports such as student learning outcomes, the inability of the community to keep their children successful in educational institutions up to the age of compulsory education. The evaluation system, education management and what is most often highlighted by the mass media today is the problem of the concept of Freedom to Learn and Freedom to Teach in Science Learning through ChatGPT. The purpose of this study is to examine Freedom to Learn and Freedom to Teach in Science Learning. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this study can be seen from the aspects of affective learning and teaching models, learning methods, and self-learning methods sharing for information can facilitate the learning process in the independent curriculum, using the help of ChatGPT technology which functions to provide easiness in the process of achieving education. As part of modern technological innovation, ChatGPT has an impact on the world of education. Schools, teachers, and students can benefit from this artificial intelligence technology. ChatGPT can be a useful learning partner in implementing the Independent Curriculum.